1999
DOI: 10.1897/1551-5028(1999)018<2028:savfep>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Vegetation Fluoride Exposure Pathways to Cotton Rats on a Petrochemical-Contaminated Landfarm

Abstract: Abstract-Total fluoride (F) content of soils, vegetation, and cotton rats (Sigmodon hispidus) was measured on a landfarm contaminated with petrochemical wastes. A potentially bioavailable form of F was determined by HCl extraction of soils and vegetation. Cotton rats from the landfarm were examined for dental lesions indicative of fluorosis. Exposure pathways including dietary ingestion of unwashed vegetation and nondietary ingestion of soil associated with grooming and burrowing were evaluated. Mean bone F (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…We hypothesize that seasonally-induced changes in the feeding habits of cotton rats contribute to greater rates of soil ingestion and risks of fluorosis during winter. Modeling efforts by Schroder (1998) indicate that most uptake of fluoride compounds by cotton rats is from soil ingestion and dry matter deposition on plant material, and cool season grasses such as Bromus sp. contained higher concentrations of fluoride compared to warm season grasses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesize that seasonally-induced changes in the feeding habits of cotton rats contribute to greater rates of soil ingestion and risks of fluorosis during winter. Modeling efforts by Schroder (1998) indicate that most uptake of fluoride compounds by cotton rats is from soil ingestion and dry matter deposition on plant material, and cool season grasses such as Bromus sp. contained higher concentrations of fluoride compared to warm season grasses.…”
Section: Discussionmentioning
confidence: 99%
“…Composite soil samples were mixed and sealed in acid-washed glass jars and transported to the laboratory for analysis. Total soil fluoride was analyzed for each composite soil sample by using fusion methods as described by McQuaker and Gurney (1977) and Schroder (1998). Briefly, 0.5 g of soil was placed in a 100 ml nickel crucible and slightly moistened with deionized distilled water.…”
Section: Laboratory Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The HCl-extractable F was 4-to 25-fold greater on the sites with elevated F compared to overall mean of reference sites; total F was 10-to 60-fold greater. In a detailed investigation of a landfarm, Schroder et al [10] found elevated levels of both total F (mean of 1,954 mg/kg) and HCl-extractable F (mean of 326 mg/kg) in soil that received application of oily sludges containing HF. All five landfarms (sites A through E) had elevated levels of both forms of F, suggesting that F in soil is more prevalent on landfarms than on other types of petrochemical sites.…”
Section: Extent Of Soil Contaminationmentioning
confidence: 99%
“…Uptake of contaminants and transfer between trophic levels in small mammals for elements such as Cd, Pb, and F have been shown to occur on contaminated sites [3][4][5]. Small mammals have also been successfully used to document exposure and toxicity of both F and metals [6][7][8][9][10]. Cotton rats (Sigmodon hispidus) are indigenous to Oklahoma, USA, and serve a critical functional role in terrestrial food chains.…”
Section: Introductionmentioning
confidence: 99%